Manajemen Konflik; Evaluasi Kine Effect Of Conflict Management And Performance Evaluation On Human Resource Development At Indomaret In Walmas - Fatih, Musalas (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
This study aims to analyze the influence of conflict management and performance evaluation on human resource development in Indomaret in Walenrang Lamasi in 2024. The research method uses quantitative methods. The data research analysis used was multiple linear regression analysis. This study was conducted with 46 respondents with results showing an R2 value of 0.543 and a simultaneous significance of p<0.05, which confirms the positive influence of conflict management and performance evaluation on human resource development. Data was collected through questionnaires and data analysis using IBM SPSS Statistics. The findings of the study reveal that conflict management has a positive and significant effect on human resource development. Performance evaluation has a positive and significant effect on human resource development. Effective conflict management is expected to create a harmonious work environment, while proper performance evaluation can encourage improvement and improvement of individual competencies. This research explores how the two factors interact and contribute to the development of quality human resources, which in turn supports the achievement of organizational goals.